Motivations for a Change in Disclosure Frequency and Its Consequences: An Examination of Voluntary Quarterly Segment Disclosures - Botosan, Christine A.; Harris, Mary S. (Journal of Accounting Research, 2000)
Christine A. Botosan, Mary S. Harris, Motivations for a Change in Disclosure Frequency and Its Consequences: An Examination of Voluntary Quarterly Segment Disclosures, Journal of Accounting Research, Vol. 38, No. 2 (Autumn, 2000), pp. 329-353